Interdisciplinary Approach to Improving the Reproductive Health of Adolescents and Adults - A D Kaprin; O I Apolikhin; A V Sivkov; O I Trushina; E G Novikova; S V Mukhtarulina; V S Yudina; P D Lopukhov (Эпидемиология и вакцинопрофилактика, 2022)
Relevance. The demographic future of our country depends to a large extent on the level of fertility, which is determined by the reproductive health of the population. Aim. To conduct an analysis of the literature on the problems of reproductive health disorders among the young population and scientifically sound areas of prevention of diseases affecting the reproductive functions of the body. Results. Among the causes of reproductive health disorders, sexually transmitted infections, human papillomavirus infection, cervical cancer occupy a special place. Domestic and foreign authors agree on the importance of preventive work with adolescents and the adult population, considering it effective by optimizing reproductive behavior and forming motivation for a healthy lifestyle. Conclusion. Reproductive health can be addressed by eliminating factors that hurt the human reproductive system and preventing reproductive diseases from becoming decompensated, which can contribute to infertility. The ability to have children in the future is the foundation of commitment to prevention and treatment. Awareness of the population will prevent infection with infections that have a direct impact on the reproductive system, their timely diagnosis and treatment will make it possible to minimize the negative impact of infectious-inflammatory processes on the reproductive function of women and men.